König, Johannes (Ed.) (2012). Teachers‘ Pedagogical Beliefs. Definition and Operationalisation – Connections to Knowledge and Performance – Development and Change. - Bieri Buschor, Christine (Swiss Journal of Educational Research, 2013)
Rezension